OPTIMIZATION OF IRRIGATION IN RENTANG IRRIGATION SCHEME AREA - PRAMAWAN (NIM : 95014006), HERI
Rentang Irrigation scheme area is a technical irrigation network with commond area of 87.840 Ha covering 3 (three) districts in West Java Province, Majalengka District, Indramayu District, and Cirebon District. Different planting schedule, planting area and cropping pattern Rentang Irrigation scheme area with the block system in Majalengka District, Indramayu District, and Cirebon District which caused conflict between farmers. The problem of water shortage in Rentang Irrigation scheme area is a problem faced by farmers every year. Overall cropping intensity for Rentang Irrigation scheme area was 131% with paddy-paddy or paddy-palawija cropping pattern. Will commence operation plan of Jatigede Reservoir as water source for Rentang Irrigation scheme area, it needs to be followed up and addressed in terms of water resources management with a good water system. The method that can be done by optimizing the water balance, that are water balance in lower dam system and water balance in the dam system through rule curve inflow-outflow in the reservoir to get irrigable area and cropping intensity. In addition, optimization is done with linear programming through mathematical model in order to arrange the right cropping pattern and increase the maximum profit of agricultural product. The calculation and analysis performed for water balance optimization using 2 (two) reviews are: (1) Review 1 with cropping pattern : paddy- paddy-palawija, (2) Review 2 with cropping pattern : paddy- paddy-paddy. In addition, the calculation and analysis is also done for optimization with linear program using 2 (two) reviews are: (1) Review of constraint 1 without limitation of planting area of certain commodities, (2) Review of constraint 2 with planting area of soybean commodity in MT-3 minimum 11,419.20 Ha. In each review simulated with 6 (six) alternative cropping patterns by changing the planting schedule for every 2 weeks, with alternative I at the beginning of October (October-1). Based on the results of the calculation and analysis, the review 1, for the wet year pattern, the cropping intensity is 300%, and for the normal year pattern, the cropping intensity is 285%, while for dry year pattern, the cropping intensity is 270%. The review 2, for wet year pattern, the cropping intensity is 245%. While for optimization with linear program to get maximum profit of agricultural production, constraint 1 review for wet year pattern, the cropping intensity is 300%, and for normal year pattern, the cropping intensity is 294,44%, while for dry year pattern, the cropping intensity is 272, 22%. Review of constraint 2 for wet year pattern, the cropping intensity is 300%, and for normal year pattern, the cropping intensity is 292,96%, while for dry year pattern, the cropping intensity is 270,74%.